Ways of optimization and cost reduction of the enterprise - Baibossynov, S.B.; Nevmatulina, K.А.; Shakeyev, S.S. (KSU publ., 2020)
Object: Optimization and cost reduction of the enterprise as a type of activity are in the process of their formation and is manifested primarily in the abundance of models of both local processes and the development of “global” strategies. Methods: The analysis of activity of the enterprises of various spheres shows that, despite abundance of publications on optimization of expenses, it is seldom when enterprise can show a sample of the organization of this process. Contrariwise, the number of unprofitable enterprises indicates that there are serious problems in the organization of the system of optimization and cost reduction. The article uses content analysis. Findings: The strategy of cost optimization sets such tasks as identifying areas of cost reduction as a factor in improving economic performance, determining ways to reduce costs for the main stages of the economic cycle of the product, as well as the calculation of costs for the operating segments and production units of the enterprise. Conclusions: Taking into account that article is devoted to the optimization and, as a consequence, to cost reduction in the enterprise, the author substantiates the necessity for the optimization process and reveals the basic principles of cost optimization in the enterprise. Special attention is paid to the methods and methods of cost optimization, their advantages
Keywords: cost optimization; enterprise; cost reduction measures; cost analysis